2011
DOI: 10.1002/jps.22568
|View full text |Cite
|
Sign up to set email alerts
|

First-Pass Metabolism via UDP-Glucuronosyltransferase: a Barrier to Oral Bioavailability of Phenolics

Abstract: Glucuronidation mediated by UDP-glucuronosyltransferases (UGTs) is a significant metabolic pathway that facilitates efficient elimination of numerous endo- and xenobiotics including phenolics. UGT genetic deficiency and polymorphisms or inhibition of glucuronidation by concomitant use of drugs are associated with inherited physiological disorders or drug induced toxicities. Moreover, extensive glucuronidation can be a barrier to oral bioavailability as the first-pass glucuronidation (or premature clearance by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
236
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 263 publications
(254 citation statements)
references
References 203 publications
(325 reference statements)
10
236
0
3
Order By: Relevance
“…The phase II enzymes UGT and SULT are significant metabolic pathways for numerous endo- and xeno-biotics in the enterocytes, which are also known to interact with the ingested flavonoids and accelerate efflux transportation of flavonoids to reduce bioavailability of flavonoids [12, 22]. As shown in Figure 4(a, b), treatment of stachyose alone was able to inhibit the expression of small intestinal UGT and SULT, respectively ( p <0.05), while treatment of individual genistein caused a severe rise in UGT and SULT, compared to that in the control mice, respectively ( p <0.05).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The phase II enzymes UGT and SULT are significant metabolic pathways for numerous endo- and xeno-biotics in the enterocytes, which are also known to interact with the ingested flavonoids and accelerate efflux transportation of flavonoids to reduce bioavailability of flavonoids [12, 22]. As shown in Figure 4(a, b), treatment of stachyose alone was able to inhibit the expression of small intestinal UGT and SULT, respectively ( p <0.05), while treatment of individual genistein caused a severe rise in UGT and SULT, compared to that in the control mice, respectively ( p <0.05).…”
Section: Resultsmentioning
confidence: 99%
“…It is interesting to note that flavonoids easily undergo first-pass metabolism catalyzed by intestinal and hepatic phase II metabolic enzymes, leading to low bioavailability of flavonoids [12,13]. In addition, it was reported that long-term treatment of genistein could induce the related protein expression of first-pass metabolism in mice [14,15] and the activities of phase II metabolic enzymes in mice could be mediated by oligosaccharides [13,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…We demonstrated that UGT1A1 and UGT1A3 are the major hepatic UGTs involved in OTS167 metabolism. Among these, UGT1A1 appears to play the main role based on our experimental data and its high level of hepatic and intestinal expression (Nakamura et al, 2008;Izukawa et al, 2009;Ohno and Nakajin, 2009;Wu et al, 2011;Court et al, 2012;Harbourt et al, 2012;Rowland et al, 2013). Supporting data include high CL int Fig.…”
Section: Discussionmentioning
confidence: 71%
“…In general, the experimental conditions utilizing microsomes can be easily controlled in comparison to in vivo and in situ models. Moreover, these methods are theoretically applicable to all species and can be used to study phase I and phase II drug metabolism to get the enzyme isoforms activity profile [7,8]. There are few limitations of microsomes, for instance, they have to be supplied with co-factors like NADPH, or UDPGA for the metabolic reactions to initiate, and lack the cell membranes to mimic the physiological environment in hepatocytes [7,8].…”
mentioning
confidence: 99%
“…Moreover, these methods are theoretically applicable to all species and can be used to study phase I and phase II drug metabolism to get the enzyme isoforms activity profile [7,8]. There are few limitations of microsomes, for instance, they have to be supplied with co-factors like NADPH, or UDPGA for the metabolic reactions to initiate, and lack the cell membranes to mimic the physiological environment in hepatocytes [7,8]. In addition, it suffers from its non-physiological nature due to the absence of cellular metabolism, membrane transport and production of co-factor [3,9].…”
mentioning
confidence: 99%